2018
DOI: 10.1055/a-0650-4296
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer after negative colonoscopy in fecal immunochemical test-positive participants from a colorectal cancer screening program

Abstract: Background and study aims  Colorectal cancer (CRC) risk after a positive fecal immunochemical test (FIT) and negative colonoscopy is unknown. We aimed to ascertain the cumulative incidence of post-colonoscopy colorectal cancer (PCCRC) and the manifestation of other lesions that could explain the test positivity in individuals with a negative colonoscopy in a population screening program. Patients and method  Observational study in participants from the first round of a CRC screening program (2010 – 2012) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…32 In a recent study from Spain, 5% of those with positive FIT and negative colonoscopy had lesions detected during 42-76 months of follow-up, one third of them were significant neoplasms mostly located in the colon and rectum. 33 In a recent study from the Netherlands hemoglobin concentrations just below the FIT cutoff were highly predictive of later development and detection of advanced colorectal neoplasms. 34 Most likely the presence of early stage neoplasms accounted for a large proportion of baseline FIT results just below the cutoff.…”
Section: Discussionmentioning
confidence: 96%
“…32 In a recent study from Spain, 5% of those with positive FIT and negative colonoscopy had lesions detected during 42-76 months of follow-up, one third of them were significant neoplasms mostly located in the colon and rectum. 33 In a recent study from the Netherlands hemoglobin concentrations just below the FIT cutoff were highly predictive of later development and detection of advanced colorectal neoplasms. 34 Most likely the presence of early stage neoplasms accounted for a large proportion of baseline FIT results just below the cutoff.…”
Section: Discussionmentioning
confidence: 96%
“…Sometimes, patients present with FIT positivity after normal colonoscopy. In an observational population-based study, the incidence of developing CRC was 0.4% over a period of 4.7 years [13]. It is the author's opinion not to do FIT after a high quality normal colonoscopy as FIT can be positive due to other lesions in the gastrointestinal tract.…”
Section: Screening Programsmentioning
confidence: 99%
“…Post-colonoscopy colorectal cancer rates have been reported between 1 in 130 to 1 in 1,000 colonoscopies (32). However, the most comparable study is by Rivero-S anchez and colleagues (33) who found a rate of post-colonoscopy cancers of 0.8 per 1,000 person-years of follow-up after a negative colonoscopy. Differences in incidence rates may be partially attributed to a statistical variability due to small numbers and different lengths of follow-up.…”
Section: Discussionmentioning
confidence: 99%